1992
DOI: 10.1144/gsl.sp.1992.061.01.16
|View full text |Cite
|
Sign up to set email alerts
|

The reservoir properties and diagenesis of the Brent Group: a regional perspective

Abstract: A regional study of Brent Group diagenesis and reservoir properties has been undertaken in order to determine the main controls on porosity and permeability in the sandstone reservoirs. Data from 44 wells from block 211/7 in the north to block 3/8 in the south and spanning current depths from 6700 to 13 400 ft include 9000 porosity, permeability and grain density determinations, quantitative petrographic information from 850 thin sections, and stable isotopic and K/Ar analyses of authigenic phases. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
80
1
3

Year Published

1993
1993
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(89 citation statements)
references
References 38 publications
3
80
1
3
Order By: Relevance
“…A very similar morphological difference between early vermicular and later blocky "kaolinite" has been described repeatedly in diagenetic studies of North Sea sandstones, but without identification of the kaolin polytypes involved (Hurst & Irwin, 1982;Kantorowicz, 1984;Thomas, 1986;Glasmann et al, 1989;Haszeldine et al, 1992;Giles et al, 1992). Polytype identification in such studies is needed to determine whether these two commonly reported morphologies in fact reflect kaolinite and dickite occurrence, respectively.…”
Section: Discussionmentioning
confidence: 79%
“…A very similar morphological difference between early vermicular and later blocky "kaolinite" has been described repeatedly in diagenetic studies of North Sea sandstones, but without identification of the kaolin polytypes involved (Hurst & Irwin, 1982;Kantorowicz, 1984;Thomas, 1986;Glasmann et al, 1989;Haszeldine et al, 1992;Giles et al, 1992). Polytype identification in such studies is needed to determine whether these two commonly reported morphologies in fact reflect kaolinite and dickite occurrence, respectively.…”
Section: Discussionmentioning
confidence: 79%
“…Models of North Sea diagenesis have tended either to invoke an essentially isochemical system (e.g., Bjørlykke et al 1989;Giles et al 1992) or significant mass transfer, either from adjacent mudrocks or from Permian evaporite-carbonate successions along episodically active basin faults (e.g., Burley 1993). Recent work suggests that deep-burial diagenesis is influenced by regional flow systems related to the generation and leakage of overpressure compartments (Haszeldine et al, in press).…”
Section: Regional Implicationsmentioning
confidence: 99%
“…Precipitation of clay minerals in the pore spaces and the evolution of clays through burial and temperature were described by many authors; for instance, in the Brent Group reservoirs of the (Middle Jurassic) North Sea, the evolution of illite and kaolin morphologies with depth and temperature is well documented (Kantorowicz, 1984;Thomas, 1986;Glasmann et al, 1989;Giles et al, 1992;Haszeldine et al, 1992). Ehrenberg et al (1993) and Lanson et al (1996) showed the relationship between kaolin morphology (i.e., vermicular or blocky kaolin) and the nature of the kaolin polytype (i.e., kaolinite or dickite).…”
Section: Introduction Geological Settingmentioning
confidence: 98%